Studi Komunikasi Interpersonal dalam Film Penyalin Cahaya : Dinamika Trauma, Relasi Kuasa, Kepercayaan, dan Pengungkapan Kebenaran - Amanda Yonnie Citagami; Assyafa Rania Putri; Destya Maharani; Reginna Quena; Arsih Amalia Chandra Permata; Wiyata Wiyata (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The study aims to analyze interpersonal communication in the film Photocopier, focusing on trauma, power relations, trust, and the process of truth revelation. The film reflects a social phenomenon of sexual violence and abuse of power in a university environment. And how the protagonist copes with conflict and social pressure through interpersonal communication. This research uses a qualitative phenomenological approach and content analysis. The findings show that interpersonal communication in the film potrays the individual struggle against power dynamics, the search of support, and the articulation of truth. This study is relevant as a reflection of communication dynamics within cultural and social insitituations. In addition, this study also reflects how a sense of safety, and trust are essential factors in the tourism industry, particualry in shaping the image of destinasions that are inclusive and welcoming to all individuals.